Hubungan Pengetahuan dan Perilaku Teman Sebaya Dengan Perilaku Seks Berisiko HIV dan IMS Pada Remaja Di Kabupaten Banyuwangi - Santoso, Eko Budi (Sekolah Tinggi Ilmu Kesehatan Surabaya, 2017)
HIV/AIDS (Human Immunodeficiency Virus and Acquired Immune Deficiency Syndrome) adolescents accumulated from 1991-2014 were 71 patients, and STIs (infectious sexually transmitted infections) in 2014 were 81 patients. Causes of HIV/AIDS and STIs in adolescents due to risky sex behavior by not using condoms. The purpose of this study was to analyze factors related to sex behavior risk of HIV/AIDS and STIs in adolescents. This research was conducted to analyze factors related to sex behavior of HIV/AIDS and STI in adolescent in Banyuwangi Regency, analytical observation research design which is cross sectional with sample 120 responden. The results showed that variables related to HIV/AIDS risk behavior and IMS based on Chi-Square test were knowledge (p value = 0,010), and peer behavior (p value = 0.044). With the incidence of HIV/AIDS and STIs among adolescents, it is hoped that risk behavior control will be conducted through positive activities and increase knowledge about HIV/AIDS and STIs, and regularly conduct health education and follow health related events ie search for HIV/AIDS ambassadors. For the Health Office it is necessary to improve the development program on reproductive health among adolescents by taking an active role in conducting counseling in schools.